MICROSTRUCTURAL ORGANIZATION OF PERIODONTIUM UNDER CONDITIONS OF COMPLEX CORRECTION AGAINST THE BACKGROUND OF EXPERIMENTAL TEN-WEEK OPIOID EXPOSURE - Fik, V. B.; Podolіyk, М. V.; Matkivska, R. M.; Dmytriv, G. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
In order to develop an adequate scheme of drug correction of periodontal tissue damage on the background of long-term action of the opioid analgesic nalbuphine, experimental studies were performed using the drugs pentoxifylline and ceftriaxone. The study was performed on male rats (24), which were divided into 3 groups. And the group is a control group. Group II – administration to rats of opioid analgesic in increasing doses for 10 weeks, where the initial dose was – 0.212 mg / kg, 9-10 weeks – 0.283 mg / kg. Group III – administration of pentoxifylline (7-10 weeks) and ceftriaxone (9-10 weeks) at a dosage of 2.86 mg against a 10-week opioid effect (from 0.212 to 0.283 mg / kg). For histological examinations, fragments of the dental segment of rats were collected using complex decalcification of the hard tissues of the dental organ. Microscopic studies in animals at 10 weeks of opioid action indicated pronounced inflammatory-dystrophic changes in periodontal tissues, which were manifested by necrotic changes in the mucous membrane of the gums, dystrophic periodontal damage and vascular disorders. Drug correction with pentoxifylline and ceftriaxone on the background of ten weeks of opioid action led to a protective effect on the microstructural organization of periodontal tissues of rats. Although complete restoration of periodontal structures in comparison with the control did not occur, however, the use of etiopathogenetic treatment contributed to a certain stabilization of the inflammatory process. The results showed that the use of pentoxifylline and ceftriaxone prevented the generalized progression of dystrophic changes in the periodontium with long-term opioid action, compared with the detected pathological changes in periodontal tissues in animals under ten weeks of opioid administration without corrective action.